Pluralism in Economics: Epistemological Rationales and Pedagogical Implementation - Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper first presents a series of epistemological rationales for pluralism as a guiding concept in economic research. In doing so, it highlights the inherent uncertainty of (scientific) knowledge as well as the complex and dynamic nature of socio-economic relationships to indicate how the discussion of theoretical and applied problems in economics might benefit from a pluralist approach. Eventually, I apply the notion of pluralism in economics to questions of economic teaching and curricular design in economics.
Keywords: 330